Problems of Data Availability and Quality for COVID-19 and Older People in Low- and Middle-Income Countries. (6th October 2020) - Lloyd-Sherlock, Peter; Sempe, Lucas; McKee, Martin; Guntupalli, Aravinda
Abstract: For all health conditions, reliable age-disaggregated data are vital for both epidemiological analysis and monitoring the relative prioritization of different age groups in policy responses. This is especially essential in the case of Coronavirus Disease-2019 (COVID-19), given the strong association between age and case fatality. This paper assesses the availability and quality of age-based data on reported COVID-19 cases and deaths for low- and middle-income countries. It finds that the availability of reliable data which permit specific analyses of older people is largely absent. The paper explores the potential of excess mortality estimates as an alternative metric of the pandemic's effects on older populations. Notwithstanding some technical challenges, this may offer a better approach, especially in countries where cause of death data are unreliable.